Estimating changes in supervisory standards and their economic effects - Bassett, William F.; Lee, Seung Jung; Spiller, Thomas Popeck (Journal of Banking & Finance, 2015)
The disappointingly slow recovery in the U.S. from the depths of the financial crisis once again focused attention on the relationship between financial frictions and economic growth. Some bankers and borrowers suggested that unnecessarily tight supervisory policies were a constraint on new lending that hindered the recovery. This paper explores one aspect of supervisory policy: whether the standards used to assign commercial bank CAMELS ratings have changed materially over time (1991–2013). Models incorporating time-varying parameters or economy-wide variables suggest that standards used in the assignment of CAMELS ratings over the post-crisis period generally were in line with historical experience. Indeed, each of the models used suggests that the variation in supervisory standards has been relatively small in absolute terms over most of the sample period. However, we show that when this measure of supervisory stringency becomes elevated, it has a noticeable dampening effect on lending activity in subsequent quarters.